The role of polyhydroxyalkanoates in adaptation of Cupriavidus necator to osmotic pressure and high concentration of copper ions - Novackova, Ivana; Hrabalova, Vendula; Slaninova, Eva; Sedlacek, Petr; Samek, Ota; Koller, Martin; Krzyzanek, Vladislav; Hrubanova, Kamila; Mrazova, Katerina; Nebesarova, Jana; Obruca, Stanislav (International journal of biological macromolecules, 2022)
Polyhydroxyalkanoates (PHA) are abundant microbial polyesters accumulated in the form of intracellular granules by numerous prokaryotes primarily as storage of carbon and energy. Apart from their storage function, the presence of PHA also enhances the robustness of the microbial cells against various stressors. In this work, we investigated the role of PHA in Cupriavidus necator, a model organism concerning PHA metabolism, for adaptation to osmotic pressure and copper ions. In long-term laboratory evolution experiments, the bacterial culture was cultivated in presence of elevated doses of sodium chloride or copper ions (incubations lasted 78 passages for Cu2+ and 68 passages for NaCl) and the evolved strains were compared with the wild-type strain in terms of growth and PHA production capacity, cell morphology (investigated by various electron microscopy techniques), activities of selected enzymes involved in PHA metabolism and other crucial metabolic pathways, the chemical composition of bacterial biomass (determined by infrared and Raman spectroscopy) and also considering robustness against various stressors. The results confirmed the important role of PHA metabolism for adaptation to both tested stressors.
Keywords: chlorid sodný; ionty; Copper; Sodium Chloride; Heavy metals; osmotický tlak; Ions; Stress conditions; Osmotic stress; Cupriavidus necator; polyhydroxyalkanoáty; Osmotic Pressure; Polyhydroxyalkanoates; Adaptation; měď